Biogeography of N2 Fixation Influenced by the Western Boundary Current Intrusion in the South China Sea. Issue 10 (21st October 2019) - Lu, Yangyang; Wen, Zuozhu; Shi, Dalin; Lin, Wenfang; Bonnet, Sophie; Dai, Minhan; Kao, Shuh‐Ji
Abstract: The N2 fixation and primary production rates were measured simultaneously using 15 N2 and 13 C incubation assays in the northern South China Sea influenced by the Kuroshio intrusion (KI) seasonally. The degree of KI (KI index, range from 0 to 1) was assessed by applying an isopycnal mixing model. The water column integrated N2 fixation and primary production for stations with KI index larger than 0.5 were 463 ± 260 μmol N·m −2 ·day −1 and 62 ± 19 mmol C·m −2 ·day −1, respectively, significantly higher than those for stations with KI index lower than 0.5 (50 ± 10 μmol N·m −2 ·day −1 and 28 ± 10 mmol C·m −2 ·day −1, respectively). Trichodesmium was the dominant diazotroph at stations with KI index larger than 0.5, with 2 orders of magnitude higher nifH gene abundance than that at stations with KI index lower than 0.5. However, the highest N2 fixation rates were found in waters with moderate KI index around 0.6, suggesting that frontal zone mixing might stimulate N2 fixation. Our results demonstrated that diazotrophs (mainly Trichodesmium ) were tightly associated with the KI, which modulated the biogeographic distribution of N2 fixers. In summary, we found the transportation of Trichodesmium by KI, then, we quantified the fraction of KI and N2 fixation rates in the northern South China Sea. The results suggested that KI generated a new biogeographic regime which could significantly influence the carbon and nitrogen cycles far away from the main stream. Key Points: The oligotrophic Kuroshio Current intrusion into the South China Sea generates a new biogeographic regime characterized by high N2 fixation Trichodesmium contributes <10% of primary production yet creates a positive correlation between N2 fixation and primary production